PENERAPAN METODE PEMBELAJARAN BAGIAN DAN KESELURUHAN TERHADAP KEMAMPUAN RENANG GAYA BEBAS - Indar Setia Adi Saputra; Ribut Wahidi (STKIP Muhammadiyah Kuningan, 2020)
The selection of learning methods is influenced by several factors, some of which are the selection of learning methods according to the characteristics of the class and also the existing facilities and infrastructure. Application of Part and Overall Learning Methods to Free Style Swimming Ability, Health and Recreation Physical Education Study Program, 2020, 43 pages. The purpose of this study was to determine the ability to master the specific motion of freestyle swimming through the application of part method and whole method. This research is a non-experimental method (ex post facto). The study population was 23 students of PJKR semester 1 class C STKIP Muhammadiyah Kuningan. The sample set in this study was 23 people. The research instrument used in this study was the critical swim speed, using the CSS calculation format. The data analysis technique used the t test at the 5% significance level. To fulfill the assumptions, this research was conducted by using the analysis prerequisite test, namely the normality test, homogeneity test, t score test, and hypothesis testing. The results showed that the part method learning method had a significant effect on the freestyle swimming ability of the 1st semester PJKR students class C STKIP Muhammadiyah Kuningan. This is evidenced by the results of the calculation of the final freestyle swimming test, namely t count 22.024> t table 1.71714 with a significance level of 5%.